UTILIZATION OF CORNCOBS FOR WASTE REDUCTION AND ENTREPRENEURSHIP OPPORTUNITIES IN SLAHARWOTAN VILLAGE, LAMONGAN REGENCY - Ambrosius Resturana Afsunasa; Noviandini Intan Safitri; Alf Arira Ananta Aysya; Khalifah Berlian; Malika Aina Zafira; Candra Amrta; Fairuz Zahira; Galuh Ajeng Aridewa; Muhammad Azhar Hibatullah; Dwi Yuli Pujiastuti (Universitas Airlangga, 2026)
Slaharwotan Village is one of the areas that produces large amounts of corncob waste in Lamongan Regency, which is often discarded or burned, creating environmental and health risks. This community service program aims to address agricultural waste in Slaharwotan Village, specifically the underutilization of corncob waste, by introducing an innovative method to process corncobs into flour for dry cookie production. The community service was implemented using an educational-participatory approach involving 27 participants from Kelompok Penerima Manfaat Program Keluarga Harapan (KPM-PKH), through theory sessions, practical exercises, and evaluation. After the training, 100% of participants reached a “good” level of understanding. The program also demonstrated the technical steps for producing corncob flour and using it in cookies with basic household equipment. At least one participant showed interest in starting a home-based business. This initiative supports SDG 8 (Decent Work and Economic Growth) and SDG 12 (Responsible Consumption and Production) by reducing waste, creating entrepreneurship opportunities, and utilizing local resources. However, limited discussion of marketing strategies, pricing, and participant monitoring hindered optimal progress tracking due to time constraints. Therefore, further evaluation is needed through regular monitoring and support from community leaders, collaboration with residents who have milling equipment, and additional training on pricing and marketing to ensure the program’s sustainability.